PENERAPAN MEDIA AUDIOVISUAL DALAM MENULIS TEKS BERITA PADA SISWA SMP KRITEN KANAAN - Klara, Maria; Sulissusiawan, Ahadi; Salem, Laurensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe low writing skill grade VIII students is caused by several factors including: students attitudes that are easy to write, students write more often, so as not to focus on writing, lazy student habit. This research with the research object of SMP Kanaan which amounted to 15 students. The data were collected by several techniques, such as observation and test. Data analysis in this research is a research procedure that data in the form of written words. Data collection tool used in this research is guidance or observation and test. Audiovisual the result of observation and judgment about media usage in news writing material have better change of direction. In the first cycle the use of audiovisual media scores reached 31 with a value of 60 into the category very well. From the results of the written test on the first cycle average score 70 students with classical completeness of 46,6% and written test results on the second cycle student average score 83,9 with classical completeness of 93,3%. The improvement that students gain on each cycle proves that the use of audiovisual media on news text writing materials can be said to be effective.Â Keywords: application, audiovisual media, news teksÂ Â